The effect of business cycle expectations on the German apprenticeship market : estimating the impact of Covid-19 - Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Wittek, Bernhard [Verfasser] (My University, 2020)
"A firm's expectation about the future business cycle is an important determinant of the decision to train apprentices. As German firms typically train apprentices to either fill future skilled worker positions, or as a substitute for other types of labor, the current coronavirus crisis will have a strong and negative impact on the German economy according to the current business cycle expectations of German firms. To the extent that the training decision of a firm depends on its perception of the business cycle, we expect a downward shift in the firm's demand for apprentices and consequently also a decrease in the equilibrium number of apprenticeship contracts. We analyze German data on the apprenticeship from 2007 to 2019 and apply first differences regressions to account for unobserved heterogeneity across states and occupations, allowing us to identify the association between changes in two popular measures of business cycle expectations (the ifo Business Climate Index and the ifo Employment Barometer) and subsequent changes in the demand for apprentices, the number of new apprenticeship contracts, unfilled vacancies and unsuccessful applicants. Taking into account the most recent data on business cycle expectations up to May 2020, we estimate that the coronavirus-related decrease in firms' expectations about the business cycle can be associated with a predicted 9% decrease in firm demand for apprentices and an almost 7% decrease in the number of new apprenticeship positions in Germany in 2020 (-34,700 apprenticeship contracts; 95% confidence interval: +/- 8,800)." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; T 3 Forschungsmethoden; Ausbildungsstellenmarkt; Ausbildungsbereitschaft; Betrieb; Ausbildungsplatzangebot; Einflussfaktor; Pandemie; Infektionskrankheit; Regressionsanalyse; Prognose